The Influence of Islamic Financial Literacy, Islamic Financial Inclusion, and Financial Behavior on the Investment Decisions of Generation Z in West Java - Ajeng Nurul Fadillah; Deni Lubis (Universitas Muhammadiyah Malang, 2024)
The largest number of Generation Z in Indonesia has potential for economic development. This is because the younger generation possesses high levels of technological skills, making them promising investors and key drivers in advancing investment growth in Indonesia. This research aims to analyze the levels of Islamic financial literacy and inclusion and their influence on financial behavior and investment decisions using descriptive analysis and the SEM-PLS method. The research results indicate that the average level of Islamic financial literacy was 77.9% (well-literate) and the level of Islamic inclusion was 80.5% (high). Islamic financial literacy and Islamic financial inclusion significantly affect investment decisions while financial behavior does not significantly affect investment decisions. This study contribute to enhance the index of literacy and financial inclusion in sharia finance for the younger generation, as well as promoting participation in sustainable investments oriented towards sharia principles.